Pengembangan Kurikulum Bisnis Berbasis Syariah: Integrasi Outcome-Based Education, Kewirausahaan, dan Maqashid Syariah - Afidah Nur Aslamah; Rangga Kusum Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This conceptual article discusses the development of a sharia-based business curriculum in higher education by integrating outcome-based education, entrepreneurship pedagogy, digital business competence, updated Islamic economy data, and maqashid shariah values. The study is motivated by the growth of the global halal economy, the expansion of Islamic finance, and Indonesia's strategic position in the global Islamic economy ecosystem. Methodologically, the paper uses a structured literature review and conceptual synthesis of higher education curriculum guidelines, Islamic business education literature, policy documents, and recent industry reports. The analysis shows that a credible sharia business curriculum should redesign graduate profiles, learning outcomes, learning experiences, and assessment systems around trustworthiness, justice, transparency, social responsibility, data literacy, and consumer protection. The article contributes an updated integrative framework and visual data synthesis for universities, study programs, and lecturers who seek to strengthen sharia business education while maintaining academic quality, employability, and ethical competence.